Effects of spray-dried betalain powder from bougainvillea (Bougainvillea spectabilis) on pork tocino. - Saydoquis, Jenalee Saquilon (2018.)
Searching for an alternative colorant with preservative function in processed meat is relevant and timely as the concerns on the negative effects of sodium nitrite on the health intensifies. This study is related to other studies conducted at the School of Technology on the use of betalain extracted from Bougainvillea (Bougainvillea spectabilis) as food colorant and preservative. Specifically, this study was done to assess the effects of spray-dried betalain powder (SDBP) from Bougainvillea (Bougainvillea spectabilis) as food colorant and preservative. Specifically, this study was done to assess the effects of spray-dried betalain powder (SDBP) from Bougainvillea on pork tocino during 10 days of chilled and ambient storage. Spray-drying has recovered 74% of betalain powder which contained 104.04 mg betalain per 100 g of bracts. Three formulations which varied in the amount of SDBP in pork tocino were assessed for the most preferred formulation (MPF) by 15 panelists in two replications. The MPF had 20% (w/w) of SDBP and did not differ significantly with control in terms of moisture content and pH using two-way ANOVA at 95% level of confidence. Yeast and mold count and total plate count also signified no differences with control at P=0.05. The color of the most preferred pork tocino decreased during 10 days of ambient (27-30°C) storage, while at chilled (4-9°C) storage no change of color was observed. The most preferred pork tocino was described to have a moderately herbal flavor and chewy texture. A 9-point hedonic scale established the general acceptability of the most preferred pork tocino as like very much. Therefore, the application of SDBP as colorant in pork tocino proved to be effective until 10 days of storage under chilled conditions. However, the antimicrobial or preservative function of the SDBP must be further assessed from a purified extract of betalain.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Bougainvillea bracts powder; Bougainvillea spectabilis; Food colorant